2001
DOI: 10.1029/2001jd900247
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of interannual winter temperature variations over southwestern Europe

Abstract: Abstract.A great part of winter temperature variability over southwestern Europe (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 31 publications
(9 reference statements)
3
44
0
Order By: Relevance
“…The analysis performed in terms of percentiles showed an increase in the number of hot days and a decrease in the number of cold days, with a 99% confidence level (Brunet et al 2007). Other studies (Sáenz et al 2001b) showed similar trends (0.2-0.3°C dec -1 ) during winter, for a denser set of stations over land locations along the Cantabrian coast (reference period 1950-1996). Aravena et al (2009a) used monthly anomalies of temperatures and teleconnection indices (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) and found a significant correlation between air temperature over the Basque Country and the North Atlantic Oscillation (NAO) index.…”
Section: Introductionmentioning
confidence: 57%
“…The analysis performed in terms of percentiles showed an increase in the number of hot days and a decrease in the number of cold days, with a 99% confidence level (Brunet et al 2007). Other studies (Sáenz et al 2001b) showed similar trends (0.2-0.3°C dec -1 ) during winter, for a denser set of stations over land locations along the Cantabrian coast (reference period 1950-1996). Aravena et al (2009a) used monthly anomalies of temperatures and teleconnection indices (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) and found a significant correlation between air temperature over the Basque Country and the North Atlantic Oscillation (NAO) index.…”
Section: Introductionmentioning
confidence: 57%
“…The associations with these two dominant modes of atmospheric variability in SW Europe (Sáenz et al 2001) were unstable since the correlations with the Scandinavian index peaked in the 1967-1986 period, whereas the NAO effects have changed from positive to negative. This transition was clearer for the western declining sites than elsewhere which suggests some connection between atmospheric variability and silver-fir dieback (Camarero 2011).…”
Section: Climate-growth Associations: the Critical Rolementioning
confidence: 99%
“…Many studies have been published relating changes in Mediterranean air temperature regimes to the largescale atmospheric circulation (Corte-Real et al, 1995, 1998Reddaway and Bigg, 1996;Hurrell and van Loon, 1997;Kutiel and Maheras, 1998;Maheras et al, 1999;Saenz et al, 2001;Kutiel and Benaroch, 2002;Xoplaki, 2002;Xoplaki et al, 2002). Some of these papers evaluated the fraction of air temperature variability explained by major sea-level pressure (SLP) and/or upper-air large-scale anomalies.…”
Section: Introductionmentioning
confidence: 99%